The Relation of Factors XII, XI, and IX to Hypercoagulable States - Thomas, Duncan P; Wessler, Stanford; Reimer, Stanley M (Thrombosis and Haemostasis, 1963)
Evidence has been obtained in rabbits that the reduction of the silicone whole blood clotting time to the normal glass range reflects a hypercoagulable state attributable to circulating activated factors XII and XI. The potential clinical implications of these findings are discussed.